Towards a better understanding of preimplantation genetic screening for aneuploidy: insights from a virtual trial for women under the age of 40 when transferring embryos one at a time - Paul N. Scriven (BMC, 2017)
Abstract Background The aim of this theoretical study is to explore the cost-effectiveness of aneuploidy screening in a UK setting for every woman aged under the age of 40 years when fresh and vitrified-warmed embryos are transferred one at a time in a first full cycle of assisted conception. Methods It is envisaged that a 24-chromosome genetic test for aneuploidy could be used to exclude embryos with an abnormal test result from transfer, or used only to rank embryos with the highest potential to be viable; the effect on cumulative outcome is assessed. The cost associated with one additional live birth event and one clinical miscarriage avoided is estimated, and the time taken to complete a cycle considered. The numbers of individual woman for whom testing is likely to be beneficial or detrimental is also evaluated. Results Adding aneuploidy screening to a first treatment cycle is unlikely to result in a higher chance of a live birth event, and can be detrimental for some women. Premature termination of a clinical trial is likely to be biased in favour of genetic testing. Testing is likely to be an expensive way of reducing the chance of clinical miscarriage and shortening treatment time without a substantial reduction in the cost of testing, and is likely to benefit a minority of women. Selecting out embryos is likely to reduce the treatment time for women whether or not they have a baby, whilst ranking embryos only to reduce the time for those that have a child and not for those who need another stimulated cycle. Conclusions Adding aneuploidy screening to IVF treatment for women under the age of 40 years is unlikely to be beneficial for most women. To achieve an unbiased assessment of the cost-effectiveness of genetic testing for aneuploidy, clinical trials need to take account of women who still have embryos available for transfer at the end of the study period. Specifying the proportions of women for whom testing is likely to be beneficial and detrimental may help better inform couples who might be considering adding aneuploidy screening to their treatment cycle.